2021
DOI: 10.3389/fpubh.2020.567337
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Empathy Disposition and Risk Perception on the Psychological Impact of Lockdown During the Coronavirus Disease Pandemic Outbreak

Abstract: During the current COVID-19 pandemic, and especially in the absence of availability of an effective treatment or a vaccine, the main health measure is neither chemical nor biological, but behavioral. To reduce the exponential growth of infections due to the new coronavirus (SARS-CoV-2) and the resulting overburdening of the healthcare system, many European Countries, parts of the US and Switzerland gradually implemented measures of quarantine and isolation defined as lockdown. This consideration leads to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
12
0
3
Order By: Relevance
“…Finally, research suggests that the willingness to adhere to the quarantine and lockdown measures is more prominent in individuals perceiving the threat as more dangerous (Dryhurst et al, 2020) and among those who have pronounced prosocial traits (Pfattheicher et al, 2020). As a result of this association, those individuals might also experience a better adaptation to the measures of restriction of freedom and better mental health (Grignoli et al, 2021;Petrocchi et al, 2021). Therefore, following the above mentioned considerations, we conjectured that:…”
Section: The Association Between Covid-19 Direct Exposure and Distressmentioning
confidence: 90%
See 2 more Smart Citations
“…Finally, research suggests that the willingness to adhere to the quarantine and lockdown measures is more prominent in individuals perceiving the threat as more dangerous (Dryhurst et al, 2020) and among those who have pronounced prosocial traits (Pfattheicher et al, 2020). As a result of this association, those individuals might also experience a better adaptation to the measures of restriction of freedom and better mental health (Grignoli et al, 2021;Petrocchi et al, 2021). Therefore, following the above mentioned considerations, we conjectured that:…”
Section: The Association Between Covid-19 Direct Exposure and Distressmentioning
confidence: 90%
“…Utility of the Lockdown Participants were asked to indicate their perceived utility of the lockdown to stop spreading COVID-19. It was evaluated with 3 items, developed ad-hoc (Grignoli et al, 2021;Petrocchi et al, 2021), with response options on a 5-point scale ranging from "strongly false" to "strongly true". The items were: "Lockdown is not very effective to stop the spread of COVID-19", "So many people are affected by COVID-19 that lockdown is useless", and "COVID-19 is not very contagious, so lockdown is useless".…”
Section: Health-related Information Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandemics and government-mandated measures of quarantine and isolation defined as lockdown have an impact on mental health of general population (Brooks et al, 2020). People suffered from depression, anxiety, insomnia, stress, addiction symptoms, and the persistence of avoidance behaviors due to infection fears, reduced social activities, loss of accessibility to basic necessities, and financial loss during the pandemics (Brooks et al, 2020;Rossi et al, 2020;Grignoli et al, 2021). During the COVID-19 pandemic, a study of 1,210 respondents in China showed that 84.7% spent 20-24 h per day at home and experienced the rates of moderate to severe depression and anxiety of 16.5 and 28.8%, respectively (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals were recruited by phone and could decide between the paper-pencil questionnaire or the online version. This research project has been conducted in accordance with the protocol 32 , the Declaration of Helsinki, the principles of Good Clinical Practice, the Human Research Act (HRA) and the Human Research Ordinance (HRO), as well as other locally relevant regulations. The study was approved by the Cantonal Ethical Committee (N. 2020-01460 /CE3679).…”
Section: Methodsmentioning
confidence: 99%